Monitoring lower limb biomechanical asymmetry and psychological measures in athletic populations - A scoping review - Keogh, J. A.; Waddington, E. E.; Masood, Z.; Mahmood, S.; Palanisamy, A. C.; Ruder, M. C.; Karsan, S.; Bishop, C.; Jordan, M. J.; Heisz, J. J.; Kobsar, D. (Scandinavian Journal of Medicine & Science in Sports, 2023)
Background Lower limb biomechanics, including asymmetry, are frequently monitored to determine sport performance level and injury risk. However, contributing factors extend beyond biomechanical and asymmetry measures to include psychological, sociological, and environmental factors. Unfortunately, inadequate research has been conducted using holistic biopsychosocial models to characterize sport performance and injury risk. Therefore, this scoping review summarized the research landscape of studies concurrently assessing measures of lower limb biomechanics, asymmetry, and introspective psychological state (e.g., pain, fatigue, perceived exertion, stress, etc.) in healthy, competitive athletes.